2002
DOI: 10.1046/j.1365-2141.2002.03486.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene mutations and three‐dimensional structural analysis in 13 families with severe factor X deficiency

Abstract: Summary. Factor X (FX) deficiency is a rare autosomal recessive disorder. The phenotype and genotype of 15 Iranian patients with FX deficiency from 13 unrelated families with a high frequency of consanguinity were analysed. Five different assays identified four patients from three families with a discrepancy between low-FX coagulant activity (FX:C) and higher-FX antigen (FX:Ag) (a type II deficiency). The remaining 11 patients had parallel reductions of FX:C and FX:Ag (a type I deficiency). Nine different homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 33 publications
2
86
0
Order By: Relevance
“…3d). This region forms a loop composed of a b-strand K followed by an a-helix A3 [Peyvandi et al, 2002] that is close to the surface but not in close proximity to the active site (Fig. 3d).…”
Section: Mutations Within the Sp Domainmentioning
confidence: 99%
See 3 more Smart Citations
“…3d). This region forms a loop composed of a b-strand K followed by an a-helix A3 [Peyvandi et al, 2002] that is close to the surface but not in close proximity to the active site (Fig. 3d).…”
Section: Mutations Within the Sp Domainmentioning
confidence: 99%
“…The EGF structure is most often seen as one a-helix A1 and up to four b-strands B1 to B4 [Akhavan et al, 2000;Peyvandi et al, 2000Peyvandi et al, , 2002 linked by three disulfide bridges (Fig. 3b and c).…”
Section: Mutations Within the Two Egf Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies conducted in Japan reported that most patients were aged 10 years or older and presented with subcutaneous hemorrhage, epistaxis, menorrhagia, gastrointestinal bleeding, and bleeding after surgery or trauma. However, the severity of FX deficiency varies from mild to serious, and depends on the degree of residual plasma FX activity [8][9][10].…”
mentioning
confidence: 99%